Agonistic interaction between females of Crax fasciolata Spix, 1825 (Aves: Galliformes: Cracidae) - Moreira, Sandro Gonçalves (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
This paper reports the first record of agonistic interaction between females of the bared-faced curassow (Crax fasciolata Spix, 1825), that lead to the death of one of them. The event occurred in the countryside of Uberlândia municipality, Minas Gerais state, Brazil.